Draft genome sequence of a multidrug-resistant blaOXA-23-producing Acinetobacter baumannii ST381 isolate from China. Issue 4 (December 2015) - Chen, Yan; Lu, Yun; Yin, Ying; Wang, Miaojuan; Lin, Shaohua; Chen, Yu
Abstract: Acinetobacter baumannii is one of the most prevalent opportunistic pathogens causing nosocomial infections and has become a major clinical and public health concern. In this study, we present the first draft genome sequence of A. baumannii TCM206 (ST381/CC92), a multidrug-resistant isolate carrying the bla OXA-23 gene in China. We observed important resistance genes in an estimated genome size of 3, 944, 450 bp with 3694 predicted protein-coding regions. These data might facilitate further understanding of the antibiotic resistance mechanisms of A. baumannii at the genomic level.